Cerebral edema in intracerebral hemorrhage: pathogenesis, natural history, and potential treatments from translation to clinical trials - Krishnan, Kailash; Campos, Paula Bermell; Nguyen, Thanh N.; Tan, Chia Wei; Chan, Siang Liang; Appleton, Jason P.; Law, ZheKang; Hollingworth, Milo; Kirkman, Matthew A.; England, Timothy J.; Roffe, Christine; Macleod, Mary Joan; et al. (Frontiers in Stroke, 2023)
Acute Intracerebral Hemorrhage (ICH) is the most devastating stroke-subtype and is associated with significant morbidity and mortality. Poor prognosis is associated with primary brain injury from the presenting hematoma and despite advances in clinical trials of evacuation or reducing expansion, management is largely limited to supportive care and secondary prevention. Recent research has led to better understanding of the pathophysiology of cerebral edema surrounding the hematoma (perihematomal edema), identification of treatment targets and potential interventions. Some therapies have progressed to testing in phase 2 and 3 clinical trials while novel agents are in development. This review focuses on the pathogenesis of perihematomal edema, natural history, and summarizes the results of potential interventions including preclinical and clinical studies. This review also lists the gaps in current evidence and suggests directions for future trials of perihematomal edema which could potentially change clinical practice.